Is privacy a problem during bedside handovers? A practice-oriented discussion paper - Malfait, Simon (Nursing ethics, 2019)
Bedside handover is the delivery of the nurse-to-nurse handover at the patient’s bedside. Although increasingly used in nursing, nurses report many barriers for delivering the bedside handover. Among these barriers is the possibility of breaching the patient’s privacy. By referring to this concept, nurses add a legal and ethical dimension to the delivery of the bedside handover, making implementation of the method difficult or even impossible. In this discussion article, the concept of privacy during handovers is being discussed by use of observations, interviews with nurses, and interviews with patients. These findings are combined with international literature from a narrative review on the topic. We provide a practice-oriented answer in which two mutually exclusive possibilities are discussed. If bedside handover does pose problems concerning privacy, this situation is not unique in healthcare and measures can be taken during the bedside handover to safeguard the patient. If bedside handover does not pose problems concerning privacy, privacy is misused by nurses to hide professional uncertainties and/or a reluctance toward patient participation. Therefore, a possible breach of privacy—whether a justified argument or not—is not a reason for not delivering the bedside handover.